The perilous gard. - Pope, Elizabeth Marie 1917-; Cuffari, Richard 1925- (Boston Houghton Mifflin, 1974)
In 1558 while imprisoned at Elwenwood Hall, a remote castle in northern England, teenaged Kate Sutton finds herself involved in a series of mysterious events that eventually bring her to an underground labyrinth peopled by the last practitioners of druidic magic.
Keywords: Druids and druidism -- Fiction; England -- Fiction